KEUNIKAN ISTIMEWA BAHASA ARAB - -, Zahratunnisa (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2022)
Like other languages ​​in the world which have their own uniqueness , Arabic is scientifically proven to have its own advantages that make its uniqueness special . Although the number of speakers is still below some other languages, Arabic with an orderly grammatical structure, definite phonetics and beautiful rhetoric has managed to maintain its authenticity as a classical language that still exists without being affected by new cultures over time. The use of Arabic as the language of the Qur'an and Shari'a is the cause. By definition , what is officially counted as Arabic is Arabic fushhah or fluent and not the local language or ' âmmiyyah which has various dialects and has been contaminated . Through a qualitative literature study, this paper finds that behind the uniqueness of its detailed language structure, Arabic is more able to save its meanings from ambiguity than other languages